Synthesis of a stable and orally bioavailable englerin analogue. Issue 11 (1st June 2016) - Fash, David M.; Peer, Cody J.; Li, Zhenwu; Talisman, Ian J.; Hayavi, Sima; Sulzmaier, Florian J.; Ramos, Joe W.; Sourbier, Carole; Neckers, Leonard; Figg, W. Douglas; Beutler, John A.; Chain, William J.
Graphical abstract: Abstract: Synthesis of analogues of englerin A with a reduced propensity for hydrolysis of the glycolate moiety led to a compound which possessed the renal cancer cell selectivity of the parent and was orally bioavailable in mice.